Pattern of Expression of PML-RARα Transcripts in Acute Promyelocytic Leukemia Patients and Its Correlation with Overall Survival: A Retrospective Study from Western India - Gondha, Shweta; Walia, Prerna; Brahmbhatt, Beena; Patel, Jayendrakumar; Mandalia, Toral; Jethva, Disha (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia with specific molecular pathogenesis, clinical features, and treatment. It is cytogenetically characterized by translocation t (15;17) (q24;q21). The location of breakpoints within the PML gene determines the formation of distinct promyelocytic leukemia-retinoic acid receptor α (PML-RARα) transcript subtypes which have prognostic significance. Breakpoints in intron 6 result in the long (L or bcr-1) subtype, those in exon 6 produce the variant (V or bcr-2) subtype, and breakpoints in intron 3 lead to the short (S or bcr-3) subtype.Objectives The aim of our study was to determine the frequencies of the different PML-RARα transcripts in patients with APL at baseline and to investigate the impact of bcr-3 transcript as a prognostic factor on survival in newly diagnosed patients with APL.Materials and Methods A retrospective study was conducted that included 54 newly diagnosed patients with APL. Clinicopathological parameters were evaluated in all cases for prognostic significance with overall survival. Real-time quantitative polymerase chain reaction was used for the quantification of PML-RARα transcripts.Results Out of 54 patients, 53 (98.1%) patients expressed bcr-3 transcript either alone or in combination with either bcr-1 or bcr-2 transcripts. Twenty-one patients (38.9%) in our study showed expression of bcr-3 transcript only. Twenty eight (51.9%) patients in our study expressed all the three transcripts. Out of the 54 patients, 20 (37%) patients died of disease, out of which 19 patients died before completion of induction therapy. Complete remission was obtained in 34 patients (63%) after induction therapy. The survival rate for patients expressing the bcr-3 transcript alone was 66.66% as compared with 60.71% for patients expressing bcr-3 transcript in combination with other two transcripts. The survival rate for patients receiving all-trans retinoic acid (ATRA) in combination with arsenic trioxide was far better than patients receiving ATRA alone.Conclusion The total leucocyte count is an independent prognostic factor in patients with APL as it was statistically significant with overall survival in our study. The bcr transcript either alone or in combination with bcr-1 and/or bcr-2 transcripts was the most frequent pattern observed.
Keywords: acute promyelocytic leukemia; PML-RARα transcripts; bcr-3 transcript